Trigeminal ganglion transcriptome analysis in 2 rat models of medication-overuse headache reveals coherent and widespread induction of pronociceptive gene expression patterns. Issue 10 (October 2018) - Buonvicino, Daniela; Urru, Matteo; Muzzi, Mirko; Ranieri, Giuseppe; Luceri, Cristina; Oteri, Claudia; Lapucci, Andrea; Chiarugi, Alberto
Abstract : Abstract: We attempted to gather information on the pathogenesis of medication-overuse headache, as well as on the neurochemical mechanisms through which symptomatic medication overuse concurs to headache chronification. Transcriptional profiles were therefore evaluated as an index of the homeostasis of the trigeminovascular system in the trigeminal ganglion of female rats exposed for 1 month to daily oral doses of eletriptan or indomethacin. We report that both drug treatments change trigeminal ganglion gene expression to a similar extend. Of note, qualitative transcriptomic analysis shows that eletriptan and indomethacin prompt nearly identical, increased expression of genes coding for proteins involved in migraine pathogenesis and central pain sensitization such as neuropeptides, their cognate receptors, prostanoid, and nitric oxide–synthesizing enzymes, as well as TRP channels. These genes, however, were not affected in thoracic dorsal root ganglia. Of note, lowering of orofacial nociceptive thresholds, as well as forepaw hyperalgesia occurred in both indomethacin- and eletriptan-treated rats. Our study reveals that chronic rat exposure to 2 acute headache medications with completely different mechanisms of action prompts pain sensitization with highly similar induction of pronociceptive genes selectively within the trigeminal ganglion. Data further our understanding of medication-overuse headache pathogenesis and provide hints for specific mechanism–based treatment options. Abstract : Chronic rat exposure to eletriptan or indomethacin prompts similar induction of pronociceptive genes within the trigeminal ganglion, a condition explaining pathogenesis of medication-overuse headache.